2022
DOI: 10.3389/fphys.2022.1021428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity and frequency on improving cognitive performance in middle-aged and older adults with mild cognitive impairment: A pilot randomized controlled trial on the minimum physical activity recommendation from WHO

Abstract: Background: The World Health Organization physical activity guidelines recommend adults and older adults to accumulate at least 150–300 min of moderate or 75–150 min of vigorous aerobic-type physical activity weekly for health benefits including improvements of cognitive performance. However, the optimal exercise intensity and frequency for maximizing the cognitive benefits remain unclear.Purpose: We conducted a parallel, assessor-blinded, pilot randomized controlled trial to evaluate the effectiveness of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Among the excluded records, 14 articles were rejected for reasons such as no sleep outcome ( n = 4), intervention noncompliance ( n = 5), participant noncompliance ( n = 1), language noncompliance ( n = 1), result non-match the data ( n = 1), non-randomized controlled trial ( n = 1), and protocol ( n = 1). Eventually, nine randomized controlled studies ( 25–33 ) were included in the SR-MA, with eight eligible for meta-analyses. The selection process, presented using the PRISMA flowchart, is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the excluded records, 14 articles were rejected for reasons such as no sleep outcome ( n = 4), intervention noncompliance ( n = 5), participant noncompliance ( n = 1), language noncompliance ( n = 1), result non-match the data ( n = 1), non-randomized controlled trial ( n = 1), and protocol ( n = 1). Eventually, nine randomized controlled studies ( 25–33 ) were included in the SR-MA, with eight eligible for meta-analyses. The selection process, presented using the PRISMA flowchart, is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This study presents a comprehensive analysis of nine RCTs conducted between 2011 and 2022. These trials were comprised of a two-arm RCT ( 29 ), a five-arm RCT ( 25 ), a cluster RCT ( 30 ), and six parallel-group RCTs. The majority of the trials (seven out of nine) were conducted in China, while one trial was conducted in Turkey ( 26 ) and another in the United States ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study indicates that moderate exercise intensity significantly enhances VSWM in patients with MCI and AD. A recent study found that moderate to high-intensity exercise has similar beneficial effects on cognitive function in patients with cognitive impairment ( 86 ). A small number of high-intensity intervention experiments were used in our study, and all of the subjects were over 70 years old.…”
Section: Discussionmentioning
confidence: 99%